Overburden structure fracture evolution and ground pressure behavior under oblique residual coal pillars in thick seam mining - Hongwei Wang; Chengpeng Tian; Yong Liu; Yanjun Li; Meng Lu; Jianqiang Jiao; Jinyuan Bai; Zhijie Qiao (Scientific Reports)
Abstract This study investigates the complex overburden fracture movements and mining pressure evolution induced by obliquely arranged lower-slice extraction passing through residual upper-slice coal pillars in split-level fully mechanized top coal caving of extremely thick coal seams. Through integrated physical simulation, FLAC3D numerical analysis, and field monitoring, the instability mechanisms of residual pillars and their impact on strata behavior were elucidated. The internal and external fields and the evolution characteristics of the overlying strata and structure in the inclined and lower-slice working faces, respectively, were determined. Key findings include: (1) lower-slice extraction induced large-scale overburden collapse through residual pillar instability, with progressive roof structure evolution. (2) When the working face was within 15 m of the section pillar, the maximum vertical stress reached 46.7 MPa (9.9% increase), with significant pillar deformation. When the working face was below the section pillar, a crescent-shaped stress-distribution pattern was observed. (3) Varying obliquely intersecting position between the lower-slice face and the overlying pillar generated a quasi-symmetric trapezoidal fracture pattern. Structural dynamic instability induced an evolutionary sequence of asymmetric double-arch, symmetric double-arch, and single-arch internal-collapse configurations. These findings help extract extremely thick coal seams safely using the split-level fully mechanised top coal caving method.